2019
DOI: 10.1038/s41598-019-40569-8
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and physiological responses of Brachypodium distachyon to fluctuating nitrogen availability

Abstract: The Nitrogen Use Efficiency (NUE) of grain cereals depends on nitrate (NO 3 − ) uptake from the soil, translocation to the aerial parts, nitrogen (N) assimilation and remobilization to the grains. Brachypodium distachyon has been proposed as a model species to identify the molecular players and mechanisms that affects these processes, for the improvement of temperate C3 cereals. We report on the developmental, physiological and grain-characteristic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 102 publications
1
21
0
Order By: Relevance
“…We found that B. distachyon grown in high N medium had greater leaf area and shoot biomass, and comparable root length to B. distachyon grown at lower N. This fits with expected plant behavior under N limitation ( Cambui et al , 2011 ; David et al , 2019 ). The resource allocation in the case of the high 5 mM NH 4 NO 3 was greater towards shoots, compared with in the case of 0.5 mM NH 4 NO 3 , which was directed to the root system ( Fig.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We found that B. distachyon grown in high N medium had greater leaf area and shoot biomass, and comparable root length to B. distachyon grown at lower N. This fits with expected plant behavior under N limitation ( Cambui et al , 2011 ; David et al , 2019 ). The resource allocation in the case of the high 5 mM NH 4 NO 3 was greater towards shoots, compared with in the case of 0.5 mM NH 4 NO 3 , which was directed to the root system ( Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Enlargement of the EcoFAB-N to 4 ml from 2.8 ml ( Sasse et al , 2019 ) allowed maintenance of N within physiological levels ( Fig. 2A ) ( David et al , 2019 ), and relieved the sharp depletion at high (2.5 mM NH 4 NO 3 ) and low N (0.25 mM NH 4 NO 3 ) ( Supplementary Fig. S1 ) in the original 2.8 ml chamber, which led to large variability in the nutrient conditions, particularly as plants became larger (20 DAT).…”
Section: Resultsmentioning
confidence: 99%
“…Since N is a diffusible nutrient, part of the N can diffuse out of the HC and be accessible to plant roots. In order to limit this effect, we made sure that the total quantity of N introduced in the HC corresponds to the reported need for B. distachyon optimal growth (David et al ., 2019). As P is not diffusible and would thus not leach out the HC, it was put in excess.…”
Section: Resultsmentioning
confidence: 99%
“…BdNRT2 gene expression is also governed by both internal and external N status (Wang et al, 2019a). BdNRT2/3 genes are potentially involved in HATS for root NO 3 − uptake in Brachypodium distachyon (David et al, 2019). In the bdnrt2.1 mutant, HATS have been shown to be reduced by 30% (Wang et al, 2019a).…”
Section: N Uptake Transport Assimilation and Remobilization N Uptake Transport And Related Modulatorsmentioning
confidence: 99%